Bioinformatics analysis of high-intensity intermittent exercise for prevention of myocardial infarction: Bioinformatics in MI - Tan, Shihua; Lin, Chen; Li, Huarui; Peng, Fenglin (Cellular and Molecular Biology, 2024)
The mechanism of target interaction involving high-intensity interval training (HIIT) in improving prognosis of myocardial infarction (MI) remains unclear. This study aimed to establish a visual network of "HIIT-target-disease" by referring to the methods of pharmacological disease and drug bioinformatic analysis, to explore the potential targets, and key targets and predict the potential biological mechanism of high-intensity intermittent exercise in preventing and treating myocardial infarction. Public data resources such as OMIM, NCBI and GeneCards were used to find potential targets of high-intensity intermittent exercise and myocardial infarction. Key targets of overlap between exercise and disease were determined according to the Relevance score values analyzed by GeneCards. The visual network diagram of "HIIT - Multi-target-disease" was constructed by Cytoscape. A total of 4820 disease targets and 528 high-intensity intermittent exercise targets were screened out, and 444 overlapped targets were obtained, including 425 protein targets. Five core protein targets were selected: IL10, PPARA, TNF, IL6, and STAT3. It may pass PI3K-AKT signaling pathway, Insulin resistance pathway, T-cell signaling pathway, TNF signaling pathway, and JAX-STAT signaling pathway and other pathways play a role. Our study comprehensively elucidated the potential targets, key targets and molecular mechanisms of high-intensity intermittent exercise in improving the prognosis of myocardial infarction, and proved that high-intensity intermittent exercise can act on multiple targets and multiple pathways to play a good preventive and therapeutic effect on myocardial infarction, providing scientific theoretical basis for revealing the mechanism of high-intensity intermittent exercise in the prevention and treatment of cardiovascular disease.